A Comparative Analysis of Grammatical Features in News Discourse - Rafa Oktavia Ramadhani; Nabilah Firanda Ardelia; Chalimah Ramadhani (Universitas Negeri Surabaya, 2026)
News discourse employs various grammatical features to organize information, establish textual cohesion, and convey meaning effectively. This study aims to identify and compare the grammatical features used in two news articles discussing Indonesia–United States trade relations published by The Jakarta Post and Reuters. The analysis focuses on four grammatical features, namely derivational forms, connecting relationships, expletive it and there, and descriptive adjectives. This study employed a qualitative descriptive method using document analysis. The data consisted of grammatical features identified in the selected news articles, which were analyzed based on theories proposed by Yule and Bauer for derivational forms, Halliday and Hasan for connecting relationships, Quirk et al. for expletive constructions, and Greenbaum and Nelson for descriptive adjectives. The findings revealed that derivational forms were the most frequently used grammatical feature in both articles, followed by descriptive adjectives and connecting relationships, while expletive constructions occurred only rarely. The Reuters article contained a slightly higher frequency of grammatical features than The Jakarta Post article, indicating a greater use of lexical and structural complexity. The results suggest that grammatical features contribute significantly to the clarity, cohesion, and effectiveness of news discourse. This study provides insights into how different news media employ grammatical resources to present economic and political information and contributes to the broader understanding of language use in contemporary journalistic writing.